(untitled) (Nexo Revista Científica, 2021)
This paper presents the results of testing a wear-resistant ceramic coating on the work surface of an internal combustion engine (ICE) cylinder’s sleeve. A combined coating formation technology is described that consists in applying an aluminum layer to the sleeve’s work face by gas dynamic spraying and then covering this face with a ceramic layer by microarc oxidation (MAO). A tenfold reduction in the reinforced sleeve has been determined by the accelerated comparative wear rig tests of reference (new) sleeve-piston ring coupling specimens and reinforced specimens with a combined coating. The supplementation of nanoparticle admixture to MAO coating reduces the friction factor between the cylinder sleeve face and the piston ring by 25-30%. The proposed technology can be used to reinforce work surfaces of new cylinder sleeves and recover worn out ones.